Risk factors of HIV/AIDS in Sindh province, Pakistan – A Systemic Review - Yasir Akbar Jamali, Imran Ali Jamali, Shakeel Ahmed Shaikh, Wali Muhammad Mangrio, Bhanwrio Menghwar, Jamshed Warsi, Mushahid Hussain Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: - The Acquired Immunodeficiency Syndrome (AIDS) is one of the most challenging health problems in medicine today. Epidemiologic, virologic, serologic, and immunologic studies have strongly implicated that the human immunodeficiency virus (HIV) is the causal cause of this newly identified fatal disease. Although AIDS has been identified in all the major continents of the world. Methods: - We conducted a comprehensive literature search using PubMed and google scholar. Papers were included from January 2000 to December 2021. For the search strategy, combinations of the following keywords and medical subject heading (MeSH) terms were used: Risk factors of HIV in Sindh’, ‘Risk factors of AIDS in Sindh’, ‘risk factors of HIV/AIDS in Sindh, epidemic of HIV in Larkana’, ‘AIDS in children in Sindh’. Results: - The major risk factor for HIV in Sindh unsafe Injection Drug users, Hijra Sex workers, and male to male sex workers followed by heterosexual contact and blood transfusion. Larkana city was an epicenter of HIV outbreaks in the past two decades. HIV infection also spread via the renal dialysis machine in Larkana. Conclusion: - Government should take serious steps for the prevention of HIV infection and open AIDS control programs in every district of Sindh and available antiviral therapy for all patients as early as possible.